2022
DOI: 10.1016/j.ssmph.2021.101000
|View full text |Cite
|
Sign up to set email alerts
|

Roles of participation in social activities in the association between adverse childhood experiences and health among older Japanese adults

Abstract: Adverse childhood experiences (ACEs) have shown strong associations with later-life health such as depression and subjective health. Social participation is also associated with later-life health but it is unclear to what extent this could contribute to alleviating harmful impacts of ACEs, nor is it clear whether ACEs are themselves associated with later-life social participation. Thus, this study aims to understand: (1) the influence of ACEs on social participation in later life and (2) whether social partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…However, individuals exposed to childhood adversities, especially those related to parental and household environments, often face a higher risk of social exclusion in adulthood. This can result in less adaptive personality traits, more behavior problems [ 44 , 45 ], difficulties in forming and maintaining relationships [ 46 , 47 ], and weaker social skills and interpersonal trust [ 47 , 48 ]. Consequently, childhood adversities can lead to smaller and less supportive networks, increased loneliness, reduced activity participation [ 26 , 37 , 49 ], and ultimately poorer cognitive function in older age [ 26 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals exposed to childhood adversities, especially those related to parental and household environments, often face a higher risk of social exclusion in adulthood. This can result in less adaptive personality traits, more behavior problems [ 44 , 45 ], difficulties in forming and maintaining relationships [ 46 , 47 ], and weaker social skills and interpersonal trust [ 47 , 48 ]. Consequently, childhood adversities can lead to smaller and less supportive networks, increased loneliness, reduced activity participation [ 26 , 37 , 49 ], and ultimately poorer cognitive function in older age [ 26 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that people who experienced CIT encountered more difficulties in building interpersonal effectiveness, providing positive responses, or establishing boundaries in social interactions (D’Andrea et al, 2012). Evidence has also shown that early life interpersonal adversities were associated with the lack of social resources (Ferraro et al, 2016), eroding the opportunities for social engagement and acquiring social support (Nishio et al, 2022; Sperry & Widom, 2013; Su et al, 2022). Hence, it is projected a chain of risk that older adults with CIT may be more likely to withdraw from social activities and lack social support, which could further increase the risk of depression in mid-later life (Gariépy et al, 2016; Tengku Mohd et al, 2019).…”
Section: Introductionmentioning
confidence: 99%